Evolution of DELLA function and signaling in land plants. Issue 3 (11th January 2021) - Phokas, Alexandros; Coates, Juliet C.
Abstract: DELLA proteins are master growth regulators that repress responses to a group of plant growth hormones called gibberellins (GAs). Manipulation of DELLA function and signaling was instrumental in the development of high‐yielding crop varieties that saved millions from starvation during the "Green Revolution." Despite decades of extensive research, it is still unclear how DELLA function and signaling mechanisms evolved within the land plant lineage. Here, we review current knowledge on DELLA protein function with reference to structure, posttranslational modifications, downstream transcriptional targets, and protein–protein interactions. Furthermore, we discuss older and recent findings regarding the evolution of DELLA signaling within the land plant lineage, with an emphasis on bryophytes, and identify future avenues of research that would enable us to shed more light on the evolution of DELLA signaling. Unraveling how DELLA function and signaling mechanisms have evolved could enable us to engineer better crops in an attempt to contribute to mitigating the effects of global warming and achieving global food security. Abstract : DELLA protein evolution in land plants . DELLA protein‐encoding genes first appeared in the ancestor of land plants. There have been subsequent gene duplications in the vascular plant ancestor and in eudicot flowering plants, with gene losses in ferns and some flowering plant families. The transactivation ability of DELLA proteins originated in the ancestor of land plants, while canonical gibberellin (GA) signaling arose in the ancestor of vascular plants. DELLA protein regulation is well‐researched in flowering plants but more research is required to determine whether regulatory mechanisms are conserved in early‐diverging lineages. Research Highlights: DELLA genes first appeared in the common ancestor of land plants and underwent two major duplications during land plant evolution. DELLAs repress gibberellin responses in vascular plants but their function in nonvascular plants remains elusive.